Neoadjuvant treatment for breast cancer - V. F. Semiglazov; V. V. Semiglazov; R. M. Paltuev; G. A. Dashyan; T. Yu. Semiglazova; P. V. Krivorotko; A. V. Komyakhov; Zh. V. Bryantseva; K. S. Nikolaev; D. Ye. Shchedrin; A. M. Yermochenkova (Опухоли женской репродуктивной системы)
linical trials have shown that the status of the women achieving complete pathomorphological repression (CPR) of a tumor is characterized by significantly improved survival as compared to that of those who have not to an equal degree. The achievement of CPR as an intermediate marker for improved survival is chiefly observed in women with aggressive subtypes of breast cancer (BC): triple-negative and HER-2-positive. In patients with the latter subtype, addition of trastuzumab to neoadjuvant chemotherapy doubles the rate of CPR and correlates with higher survival rates. The performed clinical trials have established that neoadjuvant endocrine therapy is the most suitable treatment for patients with steroid hormone receptor overexpression. Whether it may be used in combination with targeted (anti-HER-2) therapy for estrogen and HER-2 coexpression is being investigated. Neoadjuvant therapy for suitable BC stages can accelerate the assessment of novel medications through identification of predictive biological markers for response (CPR in particular). Although standard neoadjuvant therapy gives an obvious benefit to patients with CPR, other patients with the so-called residual disease are at high recurrence risk.